Roller ski rolling resistance and its effects on elite athletes' performance - Ainegren, M.; Carlsson, P.; Tinnsten, M. (The Engineering of sport 7, Volume 2, 2008)
Modern ski-treadmills allow cross-country skiers, biathletes and ski-orienteers to test their physical fitness in a laboratory environment whilst performing classical and free-style (skating) techniques on roller skis. For elite athletes the differences in performance between test occasions are quite small, thus emphasising the importance of knowing the roller skis' rolling resistance in order to allow the correct comparison between the results from different test occasions. In this study the roller skis' rolling resistance has been measured with a fixture on the ski-treadmill. The results show that the rolling resistance is significantly influenced by temperature and weight. The study also investigates the influence of significant changes in rolling resistance on biological variables. The results show that during sub maximal exercise, heart rate, blood lactate concentration, and oxygen uptake are significantly influenced by different rolling resistances.